Respuesta :
x^3 + 4x^2 – 9x – 36
= (x^3 - 9x) + (4x^2 - 36)
= x(x^2 - 9) + 4(x^2 -9)
= (x + 4) (x^2 - 9)
= (x + 4) (x - 3) (x + 3)
Done!
= (x^3 - 9x) + (4x^2 - 36)
= x(x^2 - 9) + 4(x^2 -9)
= (x + 4) (x^2 - 9)
= (x + 4) (x - 3) (x + 3)
Done!
Answer:sdfsdfsdf
[tex](x+3)(x-3)(x+4)[/tex]
Step-by-step explanation:
[tex]x^3 + 4x^2- 9x - 36[/tex]
We factor this by grouping method, we group first two terms and last two terms,
[tex](x^3 + 4x^2)+(-9x - 36)[/tex]
Now take out GCF from each group
[tex]x^2(x+4)+-9(x+4)[/tex]
Now factor out x+4
[tex](x^2-9)(x+4)[/tex]
Now factor x^2-3^2 using a^2-b^2 formula
[tex]a^2-b^2=(a+b)(a-b)[/tex]
[tex]x^2-3^2=(x+3)(x-3)[/tex]
[tex](x+3)(x-3)(x+4)[/tex]